If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 1) = 3(x + -6) Reorder the terms: 6(1 + x) = 3(x + -6) (1 * 6 + x * 6) = 3(x + -6) (6 + 6x) = 3(x + -6) Reorder the terms: 6 + 6x = 3(-6 + x) 6 + 6x = (-6 * 3 + x * 3) 6 + 6x = (-18 + 3x) Solving 6 + 6x = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 6x + -3x = -18 + 3x + -3x Combine like terms: 6x + -3x = 3x 6 + 3x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + 3x = -18 + 0 6 + 3x = -18 Add '-6' to each side of the equation. 6 + -6 + 3x = -18 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = -18 + -6 3x = -18 + -6 Combine like terms: -18 + -6 = -24 3x = -24 Divide each side by '3'. x = -8 Simplifying x = -8
| 5x+2(x+10)=83 | | 6x+5x-2x+17x=117 | | -5.6=y-8 | | a+5+8=20 | | c=210+c | | 9(8z-5)= | | x+8=57 | | d=.75d | | 9x-14=7x+22 | | 3.16=-6n-2n | | (8)(-5)= | | -2(y+1)=16 | | 2.8=-(x+4) | | y^2+12y+17=0 | | 7.21=2*3.14r | | -6(x+10)=-24 | | -15+7-(-15)= | | 24x=50-6 | | 7.21=3.14r | | 6=2n-8 | | t=5t-2(t+2) | | 3x-7+2x=4x+3 | | 6x+3x=99 | | 2u^2-16u+31=(u-6)(u-6) | | -2.5=q-1.7 | | -4(4x+5)=-6-2(8x+7) | | 220=.5h*44 | | 2.5x-12x-7=108 | | 15x=y+400 | | 5x+5=100 | | 12+8-15=-2(3x-82) | | -1/3*(8+x)=-10/3 |